Behind the wheel safety in palliative care: a literature review. Issue 3 (6th December 2018) - Howard, Mark; Ramsenthaler, Christina
Abstract : Background: Driving is a complex activity that requires physical abilities and adequate executive and cognitive functioning. There is concern among specialist palliative care services about patients continuing to drive despite having progressive incurable illnesses, comorbidities and medications to manage their symptoms. Objectives: To determine the quality of literature available about driving that would apply to palliative care patients, specifically in relation to road test or simulated driving scores and neurocognitive testing. Method: A literature search based on systematic principles was conducted on the Ovid Medline, PsycINFO, Embase and CINAHL database up to 14 October 2018. Patient populations with life-limiting illness such as cancer, cardiorespiratory and neurological diagnoses were included. Results: 37, 546 articles were screened. 14 articles satisfied the search criteria. Six studies focused on patients with multiple sclerosis (MS). Four studies investigated driving ability in patients with Huntington's disease. The remaining four articles studied heart failure, chronic obstructive pulmonary disease (COPD), interstitial lung disease and patients with cancer. In the road test studies, 19%–47% of patients with MS and Huntington's failed the behind-the-wheel assessment. The simulated driving scores in seven studies demonstrated statistically significant differences in errors made between study participants and controls. Divided attention was found in seven studies to be associated with poorer road-test or simulated driving ability. Conclusions: This review highlights the scarcity of studies available for patients who would be known to palliative care services. For most patient groups, a battery of neurocognitive tests combined with a road-test or simulated driving assessment is still considered the best practice in determining driving safety.